CRYPSIS IN THE MUD CRAB PANOPEUS AMERICANUS SAUSSURE, 1857 (DECAPODA, PANOPEIDAE): RELATIONSHIP TO SEXUAL MATURITY - Carvalho-Batista, Abner [UNESP]; Pescinelli, Regis A. [UNESP]; Garcia, Joyce R.; Guerra, Pedro G. M.; Pardo, Luis M.; Mantelatto, Fernando L. (Brill Academic Publishers, 2015)
The present study analyses the cryptic colouration patterns in mud crabs, Panopeus americanus that live in an impacted intertidal mangrove area. The main objectives were to identify the cryptic/non-cryptic transition sizes (males and females) and their relationships to morphological and functional sexual maturity. Individuals were collected from the remnant mangrove of Araca, on the coast of Sao Sebastiao, Sao Paulo, Brazil. They were sexed, measured and classified into three colouration categories: white homogeneous, cryptic heterogeneous or dark homogeneous (non-cryptic). A logistic regression was performed to detect the size at which 50% of the population reached the dark homogeneous colouration and functional sexual maturity in females. Morphological sexual maturity for both sexes was estimated through relative growth. A progressive change from heterogeneous to dark homogeneous colouration following growth was observed. Using both analyses of maturity, we detected (1) that individuals of the white homogeneous colouration can be classified as non-reproductive and (2) that there is an overlap between the size at which 50% of females reached the dark homogeneous colouration and their functional sexual maturity (approximately 14.00 mm CW). These findings are primarily explained by ontogenetic changes in habitat use during the species' life cycle.
Keywords: Brachyura; camouflage; colour change; maturity; reproduction